2002
DOI: 10.1128/jcm.40.11.3999-4003.2002
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Evaluation of Optimal Antifungal Susceptibility Testing Conditions for Dermatophytes

Abstract: A multicenter study was conducted to define the most suitable testing conditions for antifungal susceptibility of dermatophytes. Broth microdilution MICs of clotrimazole, itraconazole, and terbinafine were determined in three centers against 60 strains of dermatophytes. The effects of inoculum density (ca. 10 3 and 10 4 CFU/ml), incubation time (3, 7, and 14 days), endpoint criteria for MIC determination (complete [MIC-0] and prominent [MIC-2] growth inhibition), and incubation temperature (28 and 37°C) on int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
115
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(132 citation statements)
references
References 28 publications
13
115
1
3
Order By: Relevance
“…However, our results disagreed from SANTOS & HAMADA 18 and from FERNANDEZ-TORRES et al 5 . In another study FERNANDEZ-TORRES et al 4 tested 508 strains belonging to 24 species of dermatophytes against conventional (itraconazole and fluconazole) and some newer antifungal agents like voriconazole and UR-9825, with similar results. This seems to support the fact that incubating for four or seven days does not have a significant effect on the MIC readings.…”
Section: Discussionsupporting
confidence: 49%
“…However, our results disagreed from SANTOS & HAMADA 18 and from FERNANDEZ-TORRES et al 5 . In another study FERNANDEZ-TORRES et al 4 tested 508 strains belonging to 24 species of dermatophytes against conventional (itraconazole and fluconazole) and some newer antifungal agents like voriconazole and UR-9825, with similar results. This seems to support the fact that incubating for four or seven days does not have a significant effect on the MIC readings.…”
Section: Discussionsupporting
confidence: 49%
“…The present results are in agreement with the findings of other investigators, who showed that the susceptibility to FCZ varies greatly from one species to another. 16,17,24 Of the topical antifungal agents, ciclopirox olamine, miconazole, piroctone olamine and tioconazole, the best results were found with tioconazole, which had the lowest geometric mean MIC and MFC values for M. gypseum, T. interdigitale and T. rubrum (Figures 2, 3 and 4). These results show that the fungicidal effect of tioconazole is greater than that of miconazole, as shown in the study by Sobue and Sekiguchi.…”
Section: Discussionmentioning
confidence: 90%
“…22 Nevertheless, not all species have the same susceptibility pattern and there is evidence that dermatophytes have become resistant to certain antimycotics. 16 Although the precise cut-off points to determine the resistance of these fungi to the different antifungal agents are not known, in this study the parameters established in the Clinical and Laboratory Standards Institute (CLSI) M38-A document for filamentous fungi were taken into consideration, which establish MIC resistance ≥ 64 μg/ml for fluconazole and MIC ≥ 8 μg/ml for itraconazole and ketoconazole. 18 Fluconazole (FCZ) was found to be the least active of all the antifungal agents evaluated (Figure 1) and this is in agreement with results published from other studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations